Knowledge of first aid in school students and teachers - Dahal, Geharaj; Vaidya, Pradeep (Journal of Nepal Health Research Council, 2022)
Background: Basic knowledge on first aid is required to every citizen. School children are best target group for giving such training. School teachers have dual responsibility on this regard. They should have adequate knowledge on first aid so that they can provide when necessary and they should have enough knowledge to train students. This study was conducted to assess the knowledge of school teachers and students and effect of first aid training. Methods: This study was conducted in school teachers and high school students of six schools in Kathmandu. Two days training on first aid was given to all participants. Knowledge on first aid was assessed through self administered 10 questionnaires before and after training. Response was recorded as ‘correct’ or ‘incorrect’ of individual question and total score obtained by individual. Responses were compared before and after training and between students and teachers also. Results: A total of 152 participants (121 students and 31 teachers) were included in the study. Average score in pretest and posttest was 5.1 ±1.56 and 8.01 ±1.49 respectively with P<.001. Majority were aware of meaning of first aid, time to perform Cardiopulmonary Resuscitation and first aid knowledge on fracture and electric shock. First aid knowledge on other incidents was not satisfactory. The training improved overall knowledge of participants. There was no difference of knowledge in students and teachers. Conclusions: First aid knowledge of school teachers and students was similar and not satisfactory. Training improves knowledge significantly. Keywords: First aid knowledge; high school students; school teachers; training.